2004
DOI: 10.1175/1520-0493(2004)132<1747:dralno>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Radar and Lightning Network Observations of a Severe Outbreak of Tropical Cyclone Tornadoes

Abstract: Data from a single Weather Surveillance Radar-1988 Doppler (WSR-88D) and the National Lightning Detection Network are used to examine the characteristics of the convective storms that produced a severe tornado outbreak, including three tornadoes that reached F3 intensity, within Tropical Storm Beryl's remnants on 16 August 1994. Comparison of the radar data with reports of tornadoes suggests that only 13 cells produced the 29 tornadoes that were documented in Georgia and the Carolinas on that date. Six of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 25 publications
(36 reference statements)
11
63
0
Order By: Relevance
“…If these flows fail to create inland fields of boulders, a tornado moves the stones, as did a waterspout in New Zealand (de Lange et al 2006). The boulders move southward because the front-right quadrants of hurricanes commonly contain tornadoes (Novlan and Gray 1974) that move in the same direction as the vortex winds (McCaul 1987;McCaul et al 2004). As the hurricane moves west of Anegada the vortex winds of its trailing quadrant drive a storm surge ashore from the south.…”
Section: Tsunami or Storm?mentioning
confidence: 99%
“…If these flows fail to create inland fields of boulders, a tornado moves the stones, as did a waterspout in New Zealand (de Lange et al 2006). The boulders move southward because the front-right quadrants of hurricanes commonly contain tornadoes (Novlan and Gray 1974) that move in the same direction as the vortex winds (McCaul 1987;McCaul et al 2004). As the hurricane moves west of Anegada the vortex winds of its trailing quadrant drive a storm surge ashore from the south.…”
Section: Tsunami or Storm?mentioning
confidence: 99%
“…TCTs are also potentially hazardous at inland locations in front of a TCs projected trajectory where residents may not yet be expecting severe weather (Spratt et al 1997;McCaul et al 2004). Furthermore, Brommer and Senkbeil (2010) reported that TCTs are less of an influence, compared to storm intensity and geometric size, storm surge, and rainfall, on evacuation decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the risk of TCTs might not be a significant factor in evacuation decisions, they do have the potential to significantly impact nonevacuees along with evacuees en route and at their temporary destination. McCaul et al (2004), for instance, noted that residents of coastal Texas evacuated inland to locations that subsequently experienced numerous strong TCTs associated with Hurricane Allen (1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant differences in the relative magnitudes of moisture, instability, shear and lift in conditions preceding TC tornadoes 29 . The smaller-scale boundaries associated with TC tornadoes are distinctly different from those of large-scale extratropical cyclones in spring and late autumn 30 . TC tornadoes are also associated with stronger lower troposheric vertical shear compared with those on the Great Plains 29 , which explains the stronger (weaker) and more (less) identifiable influence of SHEAR (VWSH), particularly for F2-F5 tornadoes.…”
Section: Discussionmentioning
confidence: 77%